DEVELOPMENT OF A LOW COST OUTDOOR CARBON MONOXYDE ANALYSER APPLIED TO THE CITY OF ORAN, ALGERIA - Rahal, F; Benabadji, N; Bencherif, M; Bencherif, M. M (university of el oued/جامعة الوادي, 2021)
In Algeria, t he alternative to the absence of these air pollution measurement networks can come from the recent development of electroc hemical sensor technologies for air quality monitoring which arouses a certain interest because of their miniaturization, low energy consumption and low cost. We developed a low cost outdoor carbon monoxide analyzer called APOMOS (Air pollution Monitoring System) based on electrochemical sensor managed by microcontroller. In order to validate the APOMOS system, the recorded measurements are compared with measurements taken by a conventional analyzer. Comparison of the measurements resulting from conventiona l analyzer and those resulting from the APOMOS system gives a coefficient of determination of 98.39 %.
Article
Keywords: Air quality, carbon monoxide, electrochemical sensor, microcontroller, APOMOS.